Wissen wer wo wohnt. - Kalisch, Dominik (My University, 2012)
In cities people live together in neighbourhoods. Here they can find the infrastructure they need, starting with shops for the daily purpose to the life-cycle based infrastructures like kindergartens or nursing homes. But not all neighbourhoods are identical. The infrastructure mixture varies from neighbourhood to neighbourhood, but different people have different needs which can change e.g. based on the life cycle situation or their affiliation to a specific milieu. We can assume that a person or family tries to settle in a specific neighbourhood that satisfies their needs. So, if the residents are happy with a neighbourhood, we can further assume that this neighbourhood satisfies their needs. The socio-oeconomic panel (SOEP) of the German Institute for Economy (DIW) is a survey that investigates the economic structure of the German population. Every four years one part of this survey includes questions about what infrastructures can be found in the respondents neighbourhood and the satisfaction of the respondent with their neighbourhood. Further, it is possible to add a milieu estimation for each respondent or household. This gives us the possibility to analyse the typical neighbourhoods in German cities as well as the infrastructure profiles of the different milieus. Therefore, we take the environment variables from the dataset and recode them into a binary variable - whether an infrastructure is available or not. According to Faust (2005), these sets can also be understood, as a network of actors in a neighbourhood, which share two, three or more infrastructures. Like these networks, this neighbourhood network can also be visualized as a bipartite affiliation network and therefore analysed using correspondence analysis. We will show how a neighbourhood analysis will benefit from an upstream correspondence analysis and how this could be done. We will also present and discuss the results of such an analysis.
Keywords: Wohnungswesen; Wohnbevölkerung; Nachbarschaft; Wohnstandort; Methode; Informatik; Milieu; Bevölkerungsgruppe; Standortpräferenz; Soziales Milieu; Typisierung; Empirische Untersuchung